Newborn screening and cascade testing for FMR1 mutations12. Issue 1 (13th December 2012) - Sorensen, Page L.; Gane, Louise W.; Yarborough, Mark; Hagerman, Randi J.; Tassone, Flora
Abstract We describe an ongoing pilot project in which newborn screening (NBS) for FMR1 mutations and subsequent cascade testing are performed by the MIND Institute at the University of California, Davis Medical Center (UCDMC). To date, out of 3, 042 newborns initially screened, 44 extended family members have been screened by cascade testing of extended family members once a newborn is identified. Fourteen newborns (7 males and 7 females) and 27 extended family members (5 males and 22 females) have been identified with FMR1 mutations. Three family histories are discussed in detail, each demonstrating some benefits and risks of NBS and cascade testing for FMR1 mutations in extended family members. While we acknowledge inherent risks, we propose that with genetic counseling, clinical follow‐up of identified individuals and cascade testing, NBS has significant benefits. Treatment for individuals in the extended family who would otherwise not have received treatment can be beneficial. In addition, knowledge of carrier status can lead to lifestyle changes and prophylactic interventions that are likely to reduce the risk of late onset neurological or psychiatric problems in carriers. Also with identification of carrier family members through NBS, reproductive choices become available to those who would not have known that they were at risk to have offspring with fragile X syndrome. © 2012 Wiley Periodicals, Inc.